Pengaruh Bauran Pemasaran Terhadap Minat Berkunjung Kembali Ke Romokalisari Adventure Land Surabaya - Adistya Pramudyana; Budi Prabowo (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to determine and analyze the influence of the marketing mix on the intention to revisit Romokalisari Adventure Land Surabaya, both simultaneously and partially. This study uses independent variables (X), namely